Integrated vermin-AD technology in managing household waste in Pulau Tioman; survey on materials available for vermicomposting and analysis on plant nutrient contents of the vermicompost - Abd Aziz, Nor Azwady; Idris, Azni; Mustafa, Muskhazli; Omar, Hishamuddin; Wan Ab. Karim Ghani, Wan Azlina (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
Vermicomposting is proven to be an effective way to convert large quantities of organic waste into a high value-added product, vermicompost. Identification of suitable raw materials that are available for vermicomposting is very important to ensure the success and sustainability of the project. The initial raw material is also important factor that determine the nutrient contents of the vermicompost produced. A 30-day survey was carried out to identify the solid waste generated by the local community in Pulau Tioman that is suitable to be use in vermicomposting and analyses were done to determineplant nutrient contents of the vermicompost. The study found that almost 30% of the waste generated by the local community in PulauTioman is suitable for vermicomposting. Physico-chemical analysis showed plant nutrient and humic acid contents in vermicompost were superior compared to the control-normal compost.